THE REGENERATION OF HISTORICAL SMALL TOWN CENTERS: A METHODOLOGY FOR PARTICIPATE ACTION - Battisti, Alessandra; Cimini, Silvia (BDC. Bollettino Del Centro Calza Bini, 2015)
As European strategies on urban environment acknowledge the strengthening of community identity as a major opportunity to focus resources specifically for the energy retrofitting of historic centers and districts (Lewis et al., 2013), the aim of this study is to investigate a refurbishment model for non-monumental historical districts, which fulfills the general criteria of cultural, environmental and economic valorization, through an integrated design that combines principles of innovation and conservation, minimum intervention and energy efficiency. The refurbishment of historical villages calls for a participate action in order to deeply value the cultural heritage standing behind the historic significance of the built environment, through the development of integrated bottom-up approaches for the formulation of multi-sectoral area-based local development strategies. Keywords: multi-disciplinary approach, energy efficiency, community led local development